2012
DOI: 10.3174/ajnr.a2972
|View full text |Cite
|
Sign up to set email alerts
|

Brain Volume and Diffusion Markers as Predictors of Disability and Short-Term Disease Evolution in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE: MRI markers of neuroaxonal damage in MS have emerged as critical long-term predictors of MS-related disability. Here we investigated the potential of whole-brain diffusivity and brain volume for the prediction of cross-sectional disability and short-to medium-term clinical evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
1
18
1
Order By: Relevance
“…A majority of the studies (N = 20) recruited only relapsing-remitting (RR) MS patients [14,[16][17][18]20,23,[26][27][28]31,33,35,37,[39][40][41][42]47,48,51]. Sixteen studies recruited primary progressive (PP) MS and secondary progressive (SP) MS patients [15,21,22,24,25,29,30,32,34,36,38,[43][44][45][46]49]. The study durations ranged from 12 to 111 months.…”
Section: Overall Study Descriptionmentioning
confidence: 98%
See 2 more Smart Citations
“…A majority of the studies (N = 20) recruited only relapsing-remitting (RR) MS patients [14,[16][17][18]20,23,[26][27][28]31,33,35,37,[39][40][41][42]47,48,51]. Sixteen studies recruited primary progressive (PP) MS and secondary progressive (SP) MS patients [15,21,22,24,25,29,30,32,34,36,38,[43][44][45][46]49]. The study durations ranged from 12 to 111 months.…”
Section: Overall Study Descriptionmentioning
confidence: 98%
“…Among the 34 studies reporting EDSS at baseline, the mean scores ranged from 1.1 to 6.0 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. The reported brain volume algorithms were SIENA [14,16,17,22,24,25,[27][28][29][30][31]33,[37][38][39][41]…”
Section: Overall Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural brain imaging studies consistently found associations between cognitive deficits and wholebrain volume (1,(6)(7)(8), lesion load in the brain at T2-weighted imaging (T2 lesion load), and location of lesions in strategic white matter regions at T2-weighted imaging (9,10 …”
mentioning
confidence: 99%
“…Another imaging feature to evaluate with MRI in MS is the general neurodegenerative processes that occur in parallel, including diffuse WM changes and atrophy development, which are predictors of disability and short-term disease evolution in MS. [49][50][51] These changes can be more subtle and are not always easy to detect visually on conventional images, and therefore quantitative MR sequences can improve the assessment of these features. [52,53] Quantitative MR sequences for volumetric measurements have only recently emerged as part of standard MS imaging, and have not been implemented at all centres.…”
Section: Mri In Msmentioning
confidence: 99%